The Consistency Analysis of Planning and Budgeting Activities Program at Department of Population and Civil Registration Sukabumi Regency for Fiscal Year 2021-2023 - Gunawan Arsyad, Eriek; Saleh, Munandi; Sugiharto, Sugiharto (Lafadz Jaya Publisher, 2024)
Planning is a number of activities that are determined in advance to be carried out in a certain period in order to achieve the set goals. Planning is the most important process of all management functions because without planning other functions, organizing, directing and controlling will not be able to run. Meanwhile, the budget is a tool for the Government to direct and ensure the continuity of development, as well as improving the quality of life of the community. A budget is needed because the needs and desires of society are unlimited and continue to grow, while existing resources are limited. This research aims to determine the consistency of planning and budgeting for program activities at the Sukabumi Regency Population and Civil Registration Service for 2021-2023 using theory according to the PEACH (Public Expenditure Analysis and Capacity Harmonization) program developed by the World Bank. The research was carried out using a qualitative approach with a descriptive method with a sampling technique using a purposive sampling technique with the informants being the Head of Service, Secretary of the Service, Head of Subdivision and the Regional Budget Team (TAPD). The data collection technique used is through observation, interviews and documentation and the researcher as a human instrument. Then the data validation used is a credibility test through triangulation, namely technical triangulation, source triangulation and technical triangulation, then in data analysis the researcher reduces the data, presents the data and draws conclusions. The research results and conclusions obtained include Consistency in Planning and Budgeting for Activity Programs at the Sukabumi Regency Population and Civil Registration Service in terms of the process of preparing activity program planning and budgeting which has not been fully implemented consistently every year.